2021
DOI: 10.3390/nu13041308
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Foods and FODMAPs Containing Gluten Foods Primarily Contribute to Symptoms of Irritable Bowel Syndrome in Korean Adults

Abstract: Dietary control plays an important role in the treatment of irritable bowel syndrome (IBS). However, few studies have examined the relationship between dietary intake and symptoms of IBS in Koreans. The current cross-sectional study aimed to examine the diet in food consumption and nutrient intake in Korean adults aged 20 to 40 with IBS. The data collected were completed by 857 subjects using a community-based web survey. The questionnaire covered functional bowel disorders based on Rome III, the semi-quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…Therefore, it is difficult to restrict kimchi consumption in Korean people. A recent questionnaires-based cross-sectional study from Korea investigated the difference between the IBS group (n=186) and non-IBS group (n=671) [ 29 ]. The study found that the IBS group had significantly higher FODMAP intake than the non-IBS group (13.9 ± 9.9 g/day vs. 12.6 ± 9.7 g/day, P =0.030) [ 29 ].…”
Section: Role Of Diet In the Pathogenesis Of Ibs In Asian Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is difficult to restrict kimchi consumption in Korean people. A recent questionnaires-based cross-sectional study from Korea investigated the difference between the IBS group (n=186) and non-IBS group (n=671) [ 29 ]. The study found that the IBS group had significantly higher FODMAP intake than the non-IBS group (13.9 ± 9.9 g/day vs. 12.6 ± 9.7 g/day, P =0.030) [ 29 ].…”
Section: Role Of Diet In the Pathogenesis Of Ibs In Asian Patientsmentioning
confidence: 99%
“…A recent questionnaires-based cross-sectional study from Korea investigated the difference between the IBS group (n=186) and non-IBS group (n=671) [ 29 ]. The study found that the IBS group had significantly higher FODMAP intake than the non-IBS group (13.9 ± 9.9 g/day vs. 12.6 ± 9.7 g/day, P =0.030) [ 29 ]. Moreover, the IBS group consumed a significantly higher amount of fat than the non-IBS group (86.6 ± 55.1 g/day vs. 76.9 ± 47.9 g/day, P=0.014) [ 29 ].…”
Section: Role Of Diet In the Pathogenesis Of Ibs In Asian Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of an energy-rich diet consisting of ultraprocessed and gluten-rich foods has become predominant in the western population. 7,8 On the other hand, there has been a growing number of gluten-free diet followers who believe it has health benefits. 9,10 Nevertheless, evidence showing that gluten has harmful health effects in non-celiac subjects is scarce.…”
Section: Introductionmentioning
confidence: 99%